Developing a health-centered medical humanity education for service excellence / Haifeng Zhang ... [et al.] - Haifeng, Zhang; Abdullah, Malvern; Boo, Ho Voon; Gregory, Margaret Lucy; Yuan, Su (Universiti Teknologi MARA, Kedah, 2023)
Whether patients feel satisfied with the treatment of diseases is influenced not only by the medical technology possessed by medical personnel themselves, but also by the attitude of medical personnel toward patients, while this attitude is significantly influenced by medical humanities education. For a long time, the disease-centered medical education and training model has focused on improving medical professional skills in treating diseases, ignoring the psychological needs of patients’ health. As social development drives the need to transform the medical education model, the importance and research on medical humanities education is becoming increasingly prominent. This paper discusses the research and reform of diseasecentered to health-centered medical humanities education, finding the advantages of the health-centered medical humanities education model through research, verifying that this education model is more in line with the development of medical education and patients’ needs for medical treatment in the new era, and further exploring ways to reform the medical humanities education model that are suitable for health-centered medical humanities education. It is expected that based on this, more medical service personnel with the spirit of medical science and medical humanism in one can be cultivated in the future to meet patients’ expectations for medical care. A theoretical framework is proposed, and three hypotheses are developed for future empirical research.